2017
DOI: 10.1002/jsfa.8140
|View full text |Cite
|
Sign up to set email alerts
|

Microwave drying of germinated corn and its effect on phytochemical properties

Abstract: Drying at a microwave power of 300 W provided the highest nutritive and antioxidant values. The results of this study are useful in the selection of optimal drying conditions during microwave drying of germinated corn, as a baseline for other agricultural crops. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 40 publications
(43 reference statements)
12
22
0
Order By: Relevance
“…Such variation in diffusivities can be explained by considering the difference in the mode of energy transfer among different processes. Similar variations were observed for spinach, germinated corn, and kiwifruit by other workers (Bualuang et al, ; Maskan, ; Ozkan, Akbudak, & Akbudak, ). During MWD, radiative transfer of the EM energy and direct and exclusive absorption of EM energy by polar molecules, especially water, greatly accelerates the evaporation of water from plant matrix.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Such variation in diffusivities can be explained by considering the difference in the mode of energy transfer among different processes. Similar variations were observed for spinach, germinated corn, and kiwifruit by other workers (Bualuang et al, ; Maskan, ; Ozkan, Akbudak, & Akbudak, ). During MWD, radiative transfer of the EM energy and direct and exclusive absorption of EM energy by polar molecules, especially water, greatly accelerates the evaporation of water from plant matrix.…”
Section: Resultssupporting
confidence: 88%
“…Determination of anthocyanins was carried out following Lopez‐Martinez et al (). β‐Carotene content was determined following the procedure described by Bualuang et al (). ABTS radical scavenging activity was carried out according to Yim et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oraporn Bualuang et al [6] have shown the positive impact of microwave drying on the quality attributes of germinated and enhancing the antioxidant compounds present in this food product.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave drying, a relatively new technology, has been recommended as a fast and effective alternative drying technique due to low energy efficiency, simple operation and good quality of dried products [6,7]. Oraporn Bualuang et al [6] have shown the positive impact of microwave drying on the quality attributes of germinated and enhancing the antioxidant compounds present in this food product.…”
Section: Introductionmentioning
confidence: 99%